Depth Perception and Defensive System Activation in a 3-D Environment - Combe, Emmanuelle; Fujii, Naotaka (Frontiers in Psychology, 2011)
To survive, animals must be able to react appropriately (in temporal and behavioral terms) when facing a threat. One of the essential parameters considered by the defensive system is the distance of the threat, the “defensive distance.” In this study, we investigate the visual depth cues that could be considered as an alarm cue for the activation of the defensive system. For this purpose, we performed an active-escape pain task in a virtual three-dimensional environment. In two experiments, we manipulated the nature and consistency of different depth cues: vergence, linear perspective, and angular size. By measuring skin conductance responses, we characterized the situations that activated the defensive system. We show that the angular size of the predator was sufficient information to trigger responses from the defensive system, but we also demonstrate that vergence, which can delay the emotional response in inconsistent situations, is also a highly reliable cue for the activation of the defensive system.